Complexions at the Electrolyte/Electrode Interface in Solid Oxide Cells (Adv. Mater. Interfaces 18/2021). Issue 18 (23rd September 2021) - Türk, Hanna; Schmidt, Franz‐Philipp; Götsch, Thomas; Girgsdies, Frank; Hammud, Adnan; Ivanov, Danail; Vinke, Izaak C.; de Haart, L.G.J. (Bert); Eichel, Rüdiger‐A.; Reuter, Karsten; Schlögl, Robert; Knop‐Gericke, Axel; et al.
Abstract : Complexions at the Electrolyte/Electrode Interface In article number 2100967, Thomas Götsch and co‐workers reveal that a complexion is formed between the yttria‐stabilized zirconia electrolyte and lanthanum strontium manganite air electrode during the sintering process of solid oxide cells. This nanometer‐wide interlayer of self‐limited width is characterized by partial amorphization and compositional gradients. It offers a new perspective to understand the functionality as well as a potential pathway to improve performance and stability of these cells.